(untitled) (Eurasian Research Bulletin, 2023)
The development of information communication technologies, high-tech instrumentation, the need to create environmentally friendly technologies, alternative energy sources at the present stage have provided increasing demand for rare earth metals (REM), which today are the main components in the creation of new materials. The purpose of the article is to identify physical laws and mechanisms of modification of products from black and non-ferrous casting with oxide particles in nano- and ultradispersed state and the development of new composite materials on this basis materials that have a set of required operational properties